Influence of mulching on virus disease incidence, growth and yield of sweet pepper (Capsicum annuum) - Olawale Arogundade; Abiodun Salawu; Adeyemi Osijo; Kehinde T. Kareem (Poljoprivreda, 2019)
Sweet pepper is attacked by a number of viruses which cause serious yield losses for many growers. The influence of mulching on virus disease incidence in sweet pepper was studied under irrigation in NIHORT. Healthy seedlings were transplanted to the field and arranged in a randomized complete block design (RCBD). Different mulch used included air-dried leaves of Azadirachta indica (Neem), Tithonia diversifolia (Tithonia), Neem + Tithonia (w/w) and plastic mulch (white, black and yellow) while the control had no mulch. Incidence and severity of virus-like diseases on growth and yield were evaluated. Result indicated that plants grown using white plastic mulch had the lowest disease incidence of 34.43%. Plants grown with Tithonia, Neem, and Neem + Tithonia mulch had high disease incidence of 100%, 88%, and 90.60% respectively. Average virus disease severity ranged from 2.30 and 3.33 on a scale of 1-5 scoring system. Symptoms observed on symptomatic plants include mosaic, mottle, wrinkle and leaf reduction. Plots treated with black plastic mulch produced the lowest fruit weight, while the white and yellow plastic mulch induced highest fruit weight found. The results obtained showed that white and yellow plastic mulches are effective management options for viruses of sweet pepper.